Research Methods for Clinical Therapists / Applied Project Design and Analysis: Fourth Edition - Hicks Carolyn (Churchill Livingstone, 2004)
This book focuses on how to set up a research project, following good design principles, and how to analyze and interpret the data, using various statistical techniques. Preface, Acknowledgements, Basic Principles of Research, Introduction, Research Design and Statistics: Some Basic Concepts, Questionnaires and Surveys and Sampling, The Nature of the Data, Techniques of Descriptive Statistics, Testing Hypotheses, Design Your Study, Sources of Error in Research, Matching the Research Design to the statistical Test, Putting the Theory Into Practice, Writing up the Research for Publication, Reading Published Research Critically, Statistical Tests, Non-Parametrics Tests for Same and Matched Subject Designs, Parametric Tests for Same and Matched Subject Designs, Non-Parametric Tests for Different (unrelated) Subject Designs, Estimation, Research Applications, Attitude Scales, Repertory Grid Analysis, The Delphi Technique, Appendices, Glossary, Index.